Mobile phones and mobile advertising: an Asian perspective. (14th July 2006) - Li, Hairong; Lee, Ki-Young
This study examined three related issues of mobile advertising: the factors affecting the proliferation of mobile phones in some Asian countries, the strengths and weaknesses of mobile phones as an advertising medium and characteristics of mobile advertising. An exploratory study was conducted to quantify these characteristics. Although the results are tentative given the small sample size and primitive analysis, they still shed light on how mobile advertising is used. To put it in simple terms, mobile advertising is primarily a new form of direct response advertising; more Short Message Service- (SMS-) linked ads are used to engage interaction with mobile phone users than SMS ads sent directly to the mobile phones; sweepstakes and contests are widely used to stimulate response and the response rate in mobile advertising is usually higher than other forms of direct response advertising, including direct mail and banner ads. If properly used, mobile advertising can be an effective way to interact with consumers. Future research in mobile advertising also is discussed.